Molecular and functional heterogeneity of IL-10-producing CD4+ T cells. Issue 1 (December 2018) - Brockmann, Leonie; Soukou, Shiwa; Steglich, Babett; Czarnewski, Paulo; Zhao, Lilan; Wende, Sandra; Bedke, Tanja; Ergen, Can; Manthey, Carolin; Agalioti, Theodora; Geffken, Maria; Seiz, Oliver; et al.
Abstract IL-10 is a prototypical anti-inflammatory cytokine, which is fundamental to the maintenance of immune homeostasis, especially in the intestine. There is an assumption that cells producing IL-10 have an immunoregulatory function. However, here we report that IL-10-producing CD4+ T cells are phenotypically and functionally heterogeneous. By combining single cell transcriptome and functional analyses, we identified a subpopulation of IL-10-producing Foxp3neg CD4+ T cells that displays regulatory activity unlike other IL-10-producing CD4+ T cells, which are unexpectedly pro-inflammatory. The combinatorial expression of co-inhibitory receptors is sufficient to discriminate IL-10-producing CD4+ T cells with regulatory function from others and to identify them across different tissues and disease models in mice and humans. These regulatory IL-10-producing Foxp3neg CD4+ T cells have a unique transcriptional program, which goes beyond the regulation of IL-10 expression. Finally, we found that patients with Inflammatory Bowel Disease demonstrate a deficiency in this specific regulatory T-cell subpopulation. Tr1 cells are considered an immunosuppressive CD4 T cell population producing IL-10. Here the authors show that IL-10 is insufficient for Tr1 immunosuppression, define surface markers and transcriptional program of the immunosuppressive subset within Tr1, and reveal its deficiency in patients with IBD.